Characterization of Methyltestosterone Degrading Bacteria Isolated from Tilapia Masculinizing Ponds: Metabolic Intermediate, Glucose Amendments Effects, and Other Hormones Transformation - Pimvarat Srikwan (2020)
© 2020, Springer Nature Switzerland AG. 17α-Methyltestosterone (MT) is widely used synthetic androgenic steroid in the tilapia aquaculture industry for masculinization: a sex reversal process in which hormones are utilized to induce production of male fish. Although MT is beneficial for aquaculture, release of residual MT can cause adverse effects on wild organisms. The aims of this study were to identify MT-degrading bacteria and to characterize their degradation abilities under the conditions experienced in the environment. Nocardioides nitrophenolicus S303, Acinetobacter radioresistens B051, and Ochrobactrum haematophilum B052 were the most efficient MT-degrading bacterial strains, with the shortest degradation half-life of 10–70 h. The MT degradation by Acinetobacter and Ochrobactrum has not been reported before. After comparing their degradation rates and for reason of biosafety, N. nitrophenolicus S303 was selected for further study. Although this strain degraded MT and testosterones, it could not degrade estrogens (estrone, 17β-estradiol, nor 17α-ethinylestradiol). Glucose amendment did not affect the MT degradation rate. No metabolites with androgenic activity were observed after 264-h treatment with this strain under aerobic conditions. Methandrostenolone was found as the major intermediate during 39–90 h. This is the first report indicating the 1,2-dehydrogenase activity in steroid clevage in N. nitrophenolicus. Our study provides important information concerning the application of N. nitrophenolicus S303 to enhance MT degradation in the environment.